2022
DOI: 10.4274/tjo.galenos.2021.90008
|View full text |Cite
|
Sign up to set email alerts
|

Results of the School Children Ocular Biometry and Refractive Error Study in South India

Abstract: Objectives: Axial length (AL) is an important contributor to refraction, and growth curves are gaining importance in the prediction of myopia. This study aimed to profile the distribution of ocular biometry parameters and to identify correlates of spherical equivalent refraction (SE) among school children in South India. Materials and Methods: The School Children Ocular Biometry and Refractive Error study was conducted as part of a school screening program in southern I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Age and sex independently predicted AL but not myopia, consistent with previous research. 5 27 This difference may be related to compensatory changes in other refractive parameters. Significant differences in ACD and corneal curvature were also observed between boys and girls in the present study, 28 29 but corneal curvature was not associated with age, 30 which is consistent with the literature, as corneal curvature reaches adult levels by the age of 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age and sex independently predicted AL but not myopia, consistent with previous research. 5 27 This difference may be related to compensatory changes in other refractive parameters. Significant differences in ACD and corneal curvature were also observed between boys and girls in the present study, 28 29 but corneal curvature was not associated with age, 30 which is consistent with the literature, as corneal curvature reaches adult levels by the age of 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…4 Disruption of this coordination leads to refractive errors such as myopia and hyperopia. [5][6][7] Ocular biometry is partly controlled by genetic background. Previous studies have shown that many of the loci associated with refraction are also associated with axial length (AL), whereas genes associated with AL are not necessarily associated with refractive error.…”
Section: Introductionmentioning
confidence: 99%